Interactions of Quinupristin-Dalfopristin with Eight Other Antibiotics as Measured by Time-Kill Studies with 10 Strains of Staphylococcus aureus for Which Quinupristin-Dalfopristin Alone Was Not Bactericidal - Fuchs, Peter C. (American Society for Microbiology, 2001)
Quinupristin-dalfopristin (Q-D) and eight other antimicrobial agents were tested alone and in combination with Q-D in time-kill studies against 10 strains of macrolide-lincosamide-streptogramin B-resistant Staphylococcus aureus. Although Q-D is normally a bactericidal drug, it was only bacteriostatic for these isolates. Gentamicin alone was bactericidal against 7 of the 10 strains, and Q-D did not alter that killing effect. However, when vancomycin, cefepime, ceftazidime, imipenem, piperacillin-tazobactam, and ciprofloxacin were bactericidal when tested alone, the killing rates were reduced when combined with Q-D. The clinical significance of this in vitro antagonism is unknown at this time, and more studies are needed.